Justification of basic set of tools and methods of logistic controlling - Русановська, Орися Андріївна (Technology audit and production reserves, 2015)
The instrumental and methodological support of logistic controlling subsystem of the company is analyzed. A distribution logistic controlling of tools and methods by domestic and foreign scientists is overviewed. It is established that there is no generally accepted and universal set of tools and methods to logistic controlling. It is established that there is no consensus on the distribution of tools and methods into categories: tools and methods. That is often various scholars are included the tool to the tools and method of logistic controlling. A similar situation is classified for the methods. The expediency of category leveling of machine tools and methods of logistic controlling is proved. It is adopted a single set of tools/methods for logistic controlling are not separating them into categories. The necessity of forming a basic list of tools/methods for logistic controlling to implement logistic controlling subsystems in the overall system management is proved. It is identified that the proposed set of tools/methods for logistic controlling allow to fully ensuring the realization of its goals and objectives.